Aplikasi Sistem Order Jasa Graphic Designer Berbasis Web Pada PT. Decorner - Arishita Nurul Anastasia; Inge Handriani (Jurnal Ilmiah FIFO, 2018)
Decorner is a company engaged in the service of photography. In the development of its business, Decorner has a vision to provide the best service for customers and earn the trust of customers. To realize this vision, we need a means of web-based information. This facility aims to facilitate customers in making reservations photography services for a particular event. In the process of making a website, the first step is to analyze the system in the company, making the system design, design web menu structure and interface design of the web, after it determined the use of the software. In this application, the software used is Adobe Dreamweaver CS6 interface design to manufacture, MySQL as a database to store data off site and PHP scripts for the programming language. The results obtained in this application is the application of information systems web-based photography services reservation at Decorner. On the website Decorner equipped with photography package offered, the page order, the payment confirmation page and testimonials as well as the administrator to manage the content of the page or web content.